2020
DOI: 10.1177/0733464820982409
|View full text |Cite
|
Sign up to set email alerts
|

Handgrip Strength Asymmetry Is Associated With Limitations in Individual Basic Self-Care Tasks

Abstract: This investigation sought to determine the associations between handgrip strength (HGS) asymmetries and limitations in individual activities of daily living (ADL). The analytic sample included 18,468 participants from the 2006 to 2016 waves of the Health and Retirement Study. Those with HGS >10% stronger on either hand had any HGS asymmetry. Individuals with HGS >10% stronger on their dominant or non-dominant hand had dominant or non-dominant HGS asymmetry, respectively. ADL abilities were self-reported.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 20 publications
(4 reference statements)
1
36
0
Order By: Relevance
“…Several recent studies have examined strength asymmetries between hands and found that HGS asymmetry is associated with poor health and early all-cause mortality (23,24). Therefore, bilateral functional asymmetries could be another biomarker of poor muscle function (19). Yet, it remains opaque how asymmetric strength factors into chronic disease risk, particularly because persons in danger of multimorbidity may have poor muscle function.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have examined strength asymmetries between hands and found that HGS asymmetry is associated with poor health and early all-cause mortality (23,24). Therefore, bilateral functional asymmetries could be another biomarker of poor muscle function (19). Yet, it remains opaque how asymmetric strength factors into chronic disease risk, particularly because persons in danger of multimorbidity may have poor muscle function.…”
Section: Introductionmentioning
confidence: 99%
“…Asymmetric strength may represent another characteristic of muscle dysfunction before deficiencies in overall strength capacity are observed [8]. Previous investigations have revealed that asymmetric HGS is associated with diminished health and shortened longevity [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The “10% rule” was first proposed in the 1950s, indicating that the difference in HGS between dominant and non‐dominant hands was approximately 10% 17 . Numerous studies associated with HGS asymmetry applied the definition of an HGS ratio >10% 7–10,18–21 . Accordingly, HGS asymmetry was considered as an HGS ratio <0.90 or >1.10, and HGS symmetry was classified as an HGS ratio between 0.90 and 1.10 in the present study.…”
Section: Methodsmentioning
confidence: 83%
“…17 Numerous studies associated with HGS asymmetry applied the definition of an HGS ratio >10%. [7][8][9][10][18][19][20][21] Accordingly, HGS asymmetry was considered as an HGS ratio <0.90 or >1.10, and HGS symmetry was classified as an HGS ratio between 0.90 and 1.10 in the present study.…”
Section: Hgs Weakness and Asymmetry Measurementmentioning
confidence: 95%